Employing a MEMS plasma switch for conditioning high-voltage kinetic energy harvesters - Zhang, Hemin; Marty, Frédéric; Xia, Xin; Zi, Yunlong; Bourouina, Tarik; Galayko, Dimitri; Basset, Philippe (Nature communications, 2020)
Triboelectric nanogenerators have attracted wide attention due to their promising capabilities of scavenging the ambient environmental mechanical energy. However, efficient energy management of the generated high-voltage for practical low-voltage applications is still under investigation. Autonomous switches are key elements for improving the harvested energy per mechanical cycle, but they are complicated to implement at such voltages higher than several hundreds of volts. This paper proposes a self-sustained and automatic hysteresis plasma switch made from silicon micromachining, and implemented in a two-stage efficient conditioning circuit for powering low-voltage devices using triboelectric nanogenerators. The hysteresis of this microelectromechanical switch is controllable by topological design and the actuation of the switch combines the principles of micro-discharge and electrostatic pulling, without the need of any power-consuming control electronic circuits. The experimental results indicate that the energy harvesting efficiency is improved by two orders of magnitude compared to the conventional full-wave rectifying circuit. Conditioning efficiently high-voltage triboelectric nanogenerators for low-voltage applications remains a challenge. Here, the authors demonstrate two orders of magnitude improvement of the energy harvesting efficiency by applying a conditioning circuit with self-sustained and automatic hysteresis MEMS micro-plasma switches.